Exploring the forms of violence experienced by women street vendors, and the strategies they use to sustain a living, in a particular South African periurban context, Muswodi Dipeni - Mphoshomali, Phindulo (African Studies, 2025)
This research sought to explore the forms of violence experienced by women street vendors and the strategies they use to sustain a living, in a particular South African peri-urban context, Muswodi Dipeni. The research used a qualitative method to explore the forms of violence experienced by the participants who classify themselves as women street vendors. I worked with twelve women street vendor participants, sampled through non-probability sampling, using semi-structured interviews to collect data. I employed a thematic analysis approach to analyse the data. In addition to highlighting the forms of violence experienced by women street vendors, the study sought to further the feminist discourse on the informal sector and contribute to the exploration of gender dynamics in street trading. Through the use of qualitative methods, the results showed that women street vendors deal with diverse forms of violence daily, including physical, emotional, economic, customer-based violence, and structural violence. The findings revealed an intersection of women's experiences of violence, gender, economic status, and geographic location, indicating that these experiences are not solely due to their informal activities. Despite the obstacles that overshadow street vending and women street vendors face, many rely on street vending to earn income and support their families' growth. The research findings revealed that to address the obstacle of safety and security, women street vendors in Muswodi Dipeni have established solidarity groups as a tactic to enhance their safety and security. This research not only fills the knowledge gap regarding the complex nature of violence that women street vendors face, but it also contributes to the wider discourse on gender dynamics and informal work.